2011
DOI: 10.1128/jcm.02457-10
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Filter Paper Lesion Impression PCR for Secondarily Infected Ulcers and Nonulcerative Lesions Caused by Cutaneous Leishmaniasis

Abstract: We compared traditional cutaneous leishmaniasis diagnostic methods to filter paper lesion impression (FPLI) PCR for secondarily infected ulcers and nonulcerative lesions. The sensitivity and specificity of FPLI PCR for secondarily infected lesions (n ‫؍‬ 8) were 100%. In primarily nonulcerative lesions (n ‫؍‬ 15), the sensitivity of FPLI PCR was inferior to that of pooled-invasive-specimen PCR (72.7% versus 100%) (P ‫؍‬ 0.10). FPLI PCR is sensitive, specific, and unlike invasive procedures, can be used in seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 21 publications
5
32
0
3
Order By: Relevance
“…The patient was enrolled in a diagnostic study reported elsewhere, 15 and as such, she underwent lesion scraping, aspiration, and filter paper impression of all three ulcers. Material from lesion scrapings was smeared on glass slides for Giemsa-stained microscopy and assayed for detection of Leishmania (Viannia) kinetoplast DNA (kDNA) by polymerase chain reaction (PCR) as described ( Figure 1A).…”
Section: Case Reportmentioning
confidence: 99%
See 2 more Smart Citations
“…The patient was enrolled in a diagnostic study reported elsewhere, 15 and as such, she underwent lesion scraping, aspiration, and filter paper impression of all three ulcers. Material from lesion scrapings was smeared on glass slides for Giemsa-stained microscopy and assayed for detection of Leishmania (Viannia) kinetoplast DNA (kDNA) by polymerase chain reaction (PCR) as described ( Figure 1A).…”
Section: Case Reportmentioning
confidence: 99%
“…Material from lesion scrapings was smeared on glass slides for Giemsa-stained microscopy and assayed for detection of Leishmania (Viannia) kinetoplast DNA (kDNA) by polymerase chain reaction (PCR) as described ( Figure 1A). 15 Tissue fluid from lesion aspirates was inoculated into traditional Leishmania NovyMacNeal-Nicolle culture medium as described, 16 and assayed by kDNA PCR. Filter paper lesion impressions (FPLIs) were assayed by kDNA PCR as described.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…International reference strains and cultured parasites obtained from 80 patients attending our reference center were harvested, and their DNA was extracted as previously described (13). DNAs from anonymized, FPLI specimens from 70 CL lesions collected from 57 Peruvian patients were obtained as reported previously (2,3). Codes and geographical origins are presented in Table S1 in the supplemental material.…”
mentioning
confidence: 99%
“…26 They offer some advantages over biopsy techniques, including easy transportation from hospitals to diagnostic laboratories and the possibility of storing them for years when frozen and months when kept at room temperature. 11 In addition, filter papers are more likely to be favored by patients and clinics because they represent a non-invasive technique for collecting samples.…”
Section: Discussionmentioning
confidence: 99%